The Virtual Library - Sequeira, Deyanira (1994)
This article discusses the changes librarians must make in the face of a new virtual world. It is true that this profession has earned respect by finding books and answering reference questions, and cataloguing, but that is being done by machines in a very efficient way. How do we change?